The Correlation Between Self-Awareness and Psychological Well-Being on Caring Behavior - Muhammad Firdaus Ardianto; Etlidawati Etlidawati (Proceedings Series on Health & Medical Sciences, 2022)
Background: Nursing professional education aims to prepare learners to perform the functions and roles of nurses. Caring behavior is at the core of the nursing profession and is considered a fundamental indicator of the quality of nursing. Self-awareness related to the obligations and duties of being a nurse is the main indicator for a nurse to carry out caring behaviors. This self-awareness is expected to help students reach their potential and survive all academic and non-academic needs, thereby optimizing mental health. Objective: Knowing the relationship between self-awareness and psychological well-being with the caring behavior of Nurse professional students, Faculty of Health Sciences, University of Muhammadiyah Purwokerto. Method: This type of research is a quantitative research using the correlational study survey method with a cross-sectional time approach. Simple random sampling technique with a total of 59 students who are carrying out the practice of the Nurse profession by the criteria for inclusion and exclusion. The research instrument uses a questionnaire sheet. Data analysis using spearman-rank test. Results: The results showed that most of the Nurse professional students had high self-awareness (49.2%), a high level of psychological well-being (52.5%), and a high level of behavior caring (57.6%). There is a lack of self-awareness in the caring behavior of Nurse professional students with a p-value of 0.0001 (p-value < ?). There is psychological well-being with the caring behavior of Ners professional students with a p-value of 0.0001 Conclusion: Self-awareness and psychological well-being have a positive relationship with the caring behavior of students of the Nurse profession.